The long-term user experience of an m-Health application - Jakeline Karla Locatelli; Silvana Alba Scortegagna; Ana Carolina Bertoletti De Marchi (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2023)
Low user engagement in m-Health applications has been driving the use of retention techniques that aim to ensure a satisfactory long-term user experience. The aim was to understand the experience of hypertensive patients interacting with a mobile health application for 12 months. A qualitative/exploratory study was conducted after 12 months, with the same experimental group of participants as the non-randomized controlled clinical trial conducted in 2019. The mean age of the 16 participants was 57 years (SD=8), of which11 were female. All had low socioeconomic and educational levels. Content analysis showed no engagement with the m-health app over time. The main factors contributing to the lack of engagement were; inability of the user to use the app, lack of support and technical problems. When designing m-Health interventions, it is important to understand users' behavioral characteristics, motivations for treatment, level of involvement in health care, and ability to use technology.